POTENSIAL ANTIMIKROBA EKSTRAK ETIL ASETAT CANGKANG BULU BABI TERHADAP BAKTERI S. aureus DARI LUKA KAKI DIABETES - Hardani Hardani; Dhika Juliana Sukmana; Bustanul Atfal; Ajeng Dian Pertiwi (Jurnal Penelitian Pendidikan IPA, 2023)
Diabetes mellitus (DM) is a global problem that requires special treatment. One of the complications of DM is diabetic foot ulcers. The spread of diabetic wounds accompanied by ulcers is caused by the presence of S. aureus bacteria. This bacterium is known to be able to adapt to various classes of antibiotics, so it is necessary to explore new antibiotics from natural materials, one of which is sea urchins. This study was conducted to determine the antibacterial activity of ethyl acetate extract of sea urchin shells on the growth of S. aureus bacteria. This research was conducted at the Laboratory of the Medica Farma Husada Polytechnic in Mataram and the URB Laboratory of the NTB Provincial Hospital. The results of this study showed that there was the antibacterial activity of sea urchin shell extract with an inhibition zone diameter of 12 mm which was classified as strong, while Ciprofloxacin formed an inhibition zone with a diameter of 27 mm. From this study, it was concluded that sea urchin shell extract was able to inhibit the growth of S. aureus.